Correlation of hamstring muscle flexibility with dynamic balance and agility in physiotherapy students in Navi Mumbai: a correlational study - Shah, Helly Kaushik; Suryawanshi, Pranali (International Journal Of Community Medicine And Public Health, 2026)
Background: Physiotherapy students often engage in activities like exercise demonstrations, transfer techniques, and gait training that require both health-related and skill-related fitness. However, hamstring strain from extended sitting during lectures can negatively impact agility and dynamic balance, two crucial aspects of skill-related fitness required for clinical competency. Methods: 75 physiotherapy students in Navi Mumbai, ages 18 to 28, participated in a correlational study. The modified sit and reach test was used to measure hamstring flexibility, the functional reach test was used to measure dynamic balance, and the Illinois agility test was used to measure agility. The significance level for Pearson’s correlation test was set at p<0.05. Results: The average agility, dynamic balance, and hamstring flexibility scores were 19.90±2.85 seconds, 15.58±2.79 inches, and 23.96±4.38 cm, respectively. Agility displayed a mild, non-significant positive connection (r=0.12, p=0.306), whereas dynamic balance and hamstring flexibility revealed a small but significant positive correlation (r=0.235, p=0.042). Conclusions: The study concluded that in physiotherapy students, there is a weak positive correlation between hamstring flexibility and both dynamic balance and agility. These results underscore the importance of early assessment and focused flexibility training to enhance skill-related fitness within physiotherapy students.